Principles of finance with Excel - Benninga, Simon 1947-2015; Mofkadi, Tal (Oxford University Press, 2018)
Machine generated contents note: -- Part One: Capital Budgeting and Valuation -- 1. Introduction to Finance -- 2. The Time Value of Money -- Appendix 2.1. Algebraic Present Value Formulas -- Appendix 2.2. Annuity Formulas in Excel -- 3. Measures for Evaluation of Investment Opportunities -- 4. Loans and Amortization Tables -- 5. Effective Interest Rates -- 6. Capital Budgeting: Valuing Business Cash Flows -- Part Two: Portfolio Analysis and the Capital Asset Pricing Model -- 7. What is Risk? -- 8. Statistics for Portfolios -- Appendix 8.1. Downloading Data from Yahoo -- 9. Portfolio Diversification and Market Risk -- 10. Risk Diversification and the Efficient Frontier -- Appendix 10.1. Deriving the Formula for the Minimum Variance Portfolio -- Appendix 10.2. Portfolios with Three and More Assets -- 11. The Capital Asset Pricing Model (CAPM) and the Security Market Line (SML) -- 12. Measuring Investment Performance -- 13. The Security Market Line (SML) and the Cost of Capital -- Part Three: Valuing Securities -- 14. Efficient Markets--Some General Principles of Security Valuation -- 15. Bond Valuation -- 16. Stock Valuation -- Part Four: Options -- 17. Introduction to Options -- 18. Option Pricing Facts and Arbitrage -- 19. Option pricing: The Black-Scholes Formula -- Appendix 19.1 Getting Option Information from Yahoo -- 20. The Binomial Option Pricing Model -- Part Five: Excel Skills -- 21. Introduction to Excel -- 22. Graphs and Charts in Excel -- 23. Excel Functions -- 24. Using Data Tables -- 25. Using Goal Seek and Solver -- 26. Working with Dates in Excel
Revised edition of Principles of finance with Excel, 2011
Includes index
Keywords: EXCEL; Tabellenkalkulation; Finanzierung; Microsoft Excel (Computer file); Finance / Data processing; Capital assets pricing model; Investitionsrechnung / 1.1; Portfolio-Management / 1.2; CAPM / 1.3; Kapitalanlage / 1.4; Kapitalstruktur / 1.5; Dividende / 1.6; Optionspreistheorie / 1.7; PC-Software / 1.8; Software